Valley verified - Zhao, Kyla (Berkley, 2024)
"On paper, Zoe Zeng has made it in New York's fashion world. After a string of unpaid internships, she's now a fashion columnist at Chic, lives in a quaint apartment in Manhattan, and gets invited to exclusive industry events. But life in New York City isn't as chic as Zoe imagined. Her editor wants her to censor her opinions to please the big brands; she shares her "quaint" (read: small) apartment with two roommates who never let her store kimchi in the fridge; and how is she supposed to afford the designer clothes expected for those parties on her meager salary? Then one day, Zoe receives a job offer at FitPick, an app startup based in Silicon Valley. The tech salary and office perks are sweet, but moving across the country and switching to a totally new industry? Not so much. However, with her current career at a dead end, Zoe accepts the offer and swaps high fashion for high tech, haute couture for HTML. But she soon realizes that in an industry claiming to change the world for the better, not everyone's intentions are pure. With an eight-figure investment on the line, Zoe must find a way to revamp FitPick's image despite Silicon Valley's elitism and her icy colleagues. Or the company's future will go up in smoke--and hers with it."--